Social and solidarity economy Web information systems: State of the art and an interoperability framework - Malta, Mariana Curado (2014)
This paper presents the state of the art on interoperability developments for the social and solidarity economy(SSE) community web based information systems (WIS); it also presents a framework of interoperability for theSSE WIS and the developments made in a research-in-progress PhD project in the last 3 years. A search onthe bibliographic databases showed that so far there are no papers on interoperability initiatives on the SSE,so it was necessary to have other sources of information: a preliminary analysis of the WIS that support SSEactivities; and interviews with the representatives of some of the worlds most important SSE organisations.The study showed that the WIS are still not interoperable yet. In order to become interoperable a group of theSSE community has been developing a Dublin Corre Application Profile to be used by the SSE community asreference and binding to describe their resources. This paper also describes this on-going process.